PERAN KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL PADA DINAS SOSIAL KOTA BANJARMASIN - Khairunnisa Khairunnisa (Jurnal Ekonomi STIEP, 2021)
Research purposes for knowing role financial and non financial compensations in upgrade work productivity of Pegawai Negeri Sipil on Dinas Sosial Kota Banjarmasin. Component of compensation consists of salary, wage, incentive and fringe benefit. Population in this research amount 35 peoples and sample 20 peoples. Explenation tittle among them, compensation is all income being of money, direct goods or undirect receive of employes are reward or service given to agency. Work productivity is ratio between result achieved with role participation of labour unity of time. Dinas Sosial Kota Banjarmasin is agency of government to manage matter society, as help social to disaster, religion, etc.